2020
DOI: 10.3329/updcj.v10i2.50177
|View full text |Cite
|
Sign up to set email alerts
|

Management of Calcific metamorphosis by conventional Root Canal Treatment. A case report

Abstract: The calcified root canals cause many problems during endodontic treatment due to difficulty in canal orifice location, negotiation, preparation as well as consideration of operating time. Most serious problem may arise during any phase of root canal treatment procedure even taking a lot of precaution. Partial or total obliteration of pulpal chamber or root canal space is the most common consequences of a tooth which is exposed to traumatic injury. The most common presentation of such a tooth is complete or par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The deposition of secondary and tertiary dentin during the aging process causes the constriction of the pulp chamber space and, consequently, difficulties when endodontic treatment is in need. Negotiating a narrow, curved, and calcified root canal often results in an increased risk of perforation of the floor of the pulp chamber, lateral wall, and root [10,11]. The cone-beam computed tomography proved to be an efficient method for diagnosis and endodontic treatment planning for cases with dystrophic calcifications and other types of canal obliteration [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition of secondary and tertiary dentin during the aging process causes the constriction of the pulp chamber space and, consequently, difficulties when endodontic treatment is in need. Negotiating a narrow, curved, and calcified root canal often results in an increased risk of perforation of the floor of the pulp chamber, lateral wall, and root [10,11]. The cone-beam computed tomography proved to be an efficient method for diagnosis and endodontic treatment planning for cases with dystrophic calcifications and other types of canal obliteration [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Negotiating a narrow, curved, and calcified root canal often results in an increased risk of perforation of the floor of the pulp chamber, lateral wall, and root [10,11]. The cone-beam computed tomography proved to be an efficient method for diagnosis and endodontic treatment planning for cases with dystrophic calcifications and other types of canal obliteration [9,11]. Recently, Gabardo et al found an association between pulp stones and kidney stones [12].…”
Section: Introductionmentioning
confidence: 99%